Ponngamia pinnata- Rhi zobium: SPESIES SIMBIOTIK BERNILAI KONSEVASI TINGGI - Asri Insiana Putri (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2011)
Pongamia pinnata is an arboreal legume with high conservation value (Conference of The Parties to The Convention on Biological Diversity at the IX/2 nd on plants of high conservation volue criteria). Biotechnology breeding program with the selection of legume crops that have a high nitrogen use efficiency becomes an important issue to improve productivity and quality of P. pinnata.Thus the important symbiotic effectiveness test done to improve the ability of N fixation as the main element forming a plant tissues . The purpose of this study was to obtain Rhizobium strain from different P. pinannta habitats which has the highest effectiveness compared with strain Rhizobium sp. Commercial (USDA 122) and controls to P. pinnata seedlings. The parameters used are the number of nodules, plant height, root length and diameter . From this activity obtained 3 strains of Ambon and 2 strains of Banyuwangi . Strains selected on the basis of colony growth speed of Rhizobium sp.in vitro.The average number of nodules, plant height, root length and diameter of P. pinnata that are inoculated with strain AMI. AM2, AM3, Bal and Ba2 from seram, Ambon higher than from Baluran , Banyuwangi. On average, the highest number of nodules occurred in simbiose of P. pinnata) Ambon Rhizobium AM3 (50 ± 0,66) eguels P. pinnata Ambon –Rhizobium USDA 122 (50 ± 0,88); the best plant height occurred in P. pinnata Ambon-Rhizobium Ba2 (72cm ± 1,14) ; the best root length (25 cm ± 0.33) and the best stem diameter (4.0 mm ± 0.33) occurred in P. pinnata Ambon-Rhizobium AM2. The highest symbiose effectiveness value of P. pinnata-Rhizobium occureed in P. pinnata origin from Ambon with Rhizobium strain AM3 (32,45).